2021
DOI: 10.21203/rs.3.rs-944205/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent Anti-Delta Effect By a Booster Third-Dose of UB-612, a Precision-Designed SARS-CoV-2 Multitope Protein-Peptide Vaccine

Abstract: SARS-CoV-2 breakthrough infection occurs due to waning immunity time-to-vaccine, to which the globally-dominant, highly-contagious Delta variant is behind the scene. In the primary 2-dose and booster series of clinical Phase-1 trial, UB-612 vaccine, which contains S1-RBD and synthetic Th/CTL peptide pool for activation of humoral and T-cell immunity, induces substantial, prolonged viral-neutralizing antibodies that goes parallel with a long-lasting T-cell immunity; and a booster (3rd ) dose can prompt recall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In contrast, after the third booster dose, the neutralizing antibody GMT against Omicron and ancestral strain were 106 and 763 (6.3-fold loss) for BNT162b2 ( 11 ), or 850 and 2423 (2.9-fold loss) for mRNA-1273-50 μg ( 7 ). This additional evidence supports the greater extent of UB-612−elicited neutralizing antibodies across multiple SARS-CoV-2 variants particularly after 3 doses, a differentiation property of UB-612 primarily attributed to its RBD antigenic component ( 15 ).…”
Section: Main Textsupporting
confidence: 64%
See 3 more Smart Citations
“…In contrast, after the third booster dose, the neutralizing antibody GMT against Omicron and ancestral strain were 106 and 763 (6.3-fold loss) for BNT162b2 ( 11 ), or 850 and 2423 (2.9-fold loss) for mRNA-1273-50 μg ( 7 ). This additional evidence supports the greater extent of UB-612−elicited neutralizing antibodies across multiple SARS-CoV-2 variants particularly after 3 doses, a differentiation property of UB-612 primarily attributed to its RBD antigenic component ( 15 ).…”
Section: Main Textsupporting
confidence: 64%
“…Two immunizations with UB-612 were immunogenic and led to seroconversion rate of neutralizing antibody in >90% of vaccine recipients. In these same studies, UB-612 was shown to elicit long-lasting neutralizing antibody titers similar to levels detected in convalescent patients ( 15 ) and B cell and T cell responses against Delta and Omicron variants ( 14 ).…”
Section: Main Textmentioning
confidence: 60%
See 2 more Smart Citations